Q. 14 I4.5( 6 Votes )

Prove the following identities :

sin2θ – cos2 ϕ = sin2ϕ – cos2θ

Answer :

Taking LHS = sin2 θ – cos2 φ

=( 1 – cos2 θ) – (1 – sin2 φ) [ cos2 θ + sin2 θ = 1] & [ cos2 φ + sin2 φ = 1]


= 1 – cos2 θ – 1 + sin2 φ


= sin2 φ – cos2 θ


=RHS


Hence Proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Champ Quiz | Trigonometric Identities33 mins
Trigonometric Identities33 mins
NCERT | Trigonometric Identities52 mins
Quiz | Task on Trigonometric Ratios46 mins
Algebraic Identities48 mins
Quiz | Practice Important Questions on Trigonometrical Identities46 mins
Quiz on Trigonometric Ratios31 mins
T- Ratios of Specified Angles58 mins
Trick to learn all Trigonometric Formulae28 mins
Testing the T- Ratios of Specified Angles57 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses